2004
DOI: 10.1309/dk1c-g9ma-tkyy-bfmq
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Aspergillus Species in Pediatric Tissue Samples

Abstract: Definitive diagnosis of invasive aspergillosis often requires tissue samples for histologic evidence of fungal infection and culture confirmation of Aspergillus species. However, the culture frequently fails to isolate Aspergillus species. Alternative approaches to confirm Aspergillus infection use polymerase chain reaction, in situ hybridization, and immunohistochemical analysis on paraffin-embedded sections. These approaches are well characterized in animals and adult patients but not pediatric patients. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
4
14
0
2
Order By: Relevance
“…Similarly, Lee et al [13] reported that only 43 of 52 patients (83%) with histomorphologic aspergillosis had positive cultures for Aspergillus species, and the remaining 9 (17%) had cultures positive for other organisms including Scedosporium and Fusarium spp. Thus, our findings on the limitations of tissue morphology alone for diagnosing aspergillosis are consistent with previous findings [1,7,[11][12][13]. However, only limited data are available concerning the accuracy of histomorphologic diagnosis of mucormycosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Lee et al [13] reported that only 43 of 52 patients (83%) with histomorphologic aspergillosis had positive cultures for Aspergillus species, and the remaining 9 (17%) had cultures positive for other organisms including Scedosporium and Fusarium spp. Thus, our findings on the limitations of tissue morphology alone for diagnosing aspergillosis are consistent with previous findings [1,7,[11][12][13]. However, only limited data are available concerning the accuracy of histomorphologic diagnosis of mucormycosis.…”
Section: Discussionsupporting
confidence: 92%
“…Although direct comparisons are difficult because different antibodies were used in different studies, our findings are consistent with work showing that IHC could improve the sensitivity and specificity of diagnosis for systemic mycoses, especially aspergillosis [1,7,11,12]. However, there is little information on the utility of mucormycosis IHC because of the few patients with mucormycosis studied previously.…”
Section: Discussionsupporting
confidence: 84%
“…A localização da imunomarcação nas hifas observada nos casos de zigomicose (ocorrendo principalmente no citoplasma) e aspergilose (na parede, nos septos e no citoplasma) pode estar associada ao tipo de antígeno específico de cada anticorpo. De acordo com alguns autores (Jensen et al 1996b, Choi et al 2004, anticorpos contra antígenos somáticos solúveis em água (water-soluble somatic antigens -WSSA) geralmente reagem com estruturas presentes no citoplasma (componentes não estruturais), enquanto anticorpos contra antí-genos presentes nas frações da parede (wall fraction -WF) reagem com componentes estruturais presentes principalmente na parede, septos e citoplasma. A diferenciação na localização da imunomarcação auxilia na interpretação dos resultados da técnica de imuno-histoquímica para fungos, bem como para outros agentes (Ramos-Vara et al 2008).…”
Section: Discussionunclassified
“…Alguns desses estudos têm sido publicados (Jensen et al 1994, Rocha et al 1998, Choi et al 2004, Schuetz & Cohen 2009) e são de grande valor no aprimoramento do uso da IHQ para detecção e identificação de fungos na rotina em patologia veterinária.…”
Section: Introductionunclassified
“…Besides the ELISA assay, immunohistochemical galactomannan detection in FFPE tissue specimens with the aid of monoclonal antibodies is a useful tool in the diagnosis of IA [46,47].…”
Section: Galactomannanmentioning
confidence: 99%